Emotional distress of adolescents from dysfunctional families as a subject of scientific research - N. M. Nikitaev; N. A. Tsvetkova (Вестник университета, 2024)
The article provides a scientific justification for the relevance of studying emotional distress of adolescents from dysfunctional families. The social significance of the topic is noted: the emotional distress of adolescent children not only makes unhappy themselves, but also reduces the level of social health of the family and the whole society, affecting social security. The purpose of the research is a theoretical analysis of sources of scientific information which, presumably, can form a methodological basis for studying family predictors of the adolescent emotional distress. The material in the article is presented in accordance with four research questions concerning the formulation of this scientific problem, its current state in domestic and foreign social psychology, and its poorly studied aspects. The definition of the concept of the emotional distress is clarified, its similarity to the concept of emotional modality is shown; the already established features of the emotional sphere of adolescent children are noted. It is concluded that by now there are prerequisites for studying families with adolescents simultaneously from the standpoint of socio-psychological and systemic approaches. A model of empirical research of the family predictors of the emotional distress of adolescents from dysfunctional families is proposed. The prospects of practical application of the study results are outlined.